Digital non-metric image-based documentation for the preservation and restoration of mural paintings: the case of the Üzümlü Rock-hewn Church, Turkey - Ryo Higuchi; Tamaki Suzuki; Mina Shibata; Yoko Taniguchi; Murat Gülyaz (Virtual Archaeology Review)
Digital photography is a valuable documentation technique for the preservation of a cultural heritage site because highresolution photography presents both general and detailed views of mural paintings and mural condition in a single image. Advanced digital technology is particularly helpful for preserving and restoring mural paintings given that the painting condition is recorded on high-resolution base maps shows how mural paintings are damaged by environmental stresses, mechanical damages and inappropriate treatments, among others. In addition, photogrammetric software technology is rapidly advancing and being applied to the digital documentation of mural paintings or rock art. Nevertheless, human experience and investigation of mural paintings is indispensable for recording the condition of mural paintings, and this highlights that every step of documentation conducted in situ is desirable. However, images by photogrammetric software do not show sufficient resolution because most normal portable computers used on-site are not usually sufficient. Based on our experience at the Üzümlü Church in Cappadocia, Turkey, we propose a new approach to document mural conditions in situ for preservation and restoration. Our method is based on a comparison of a non-metric but approximate high-resolution image with the actual mural paintings. The method does not require special instruments and enables digital documentation of the mural condition in situ at a low cost, in a short time frame and using minimal human resources.